Blood clots affect the response of tympanic membrane perforations to gelfoam grafting after ventilation tube insertion - Zhengcai Lou (Journal of Otolaryngology - Head and Neck Surgery, 2021)
Abstract Chronic tympanic membrane (TM) perforation associated with ventilation tube (VT) insertion was commonly encountered in pediatric patients with chronic otitis media with effusion (COME) treatment and eustachian tube dysfunction. The persistent perforation require surgical closure by myringoplasty. Song JS et al. recently a paper entitled: “Evaluating short and long term outcomes following pediatric myringoplasty with gelfoam graft for tympanic membrane perforation following ventilation tube insertion.” In their study, the authors performed gelfoam myringoplasty to repair the perforations following VT insertion in children and compare the successful TM closure rate among different graft materials. The authors believed that gelfoam alone was superior to hyaluronic acid (HA), tragal cartilage (TC), and gelfoam-plus-temporal fascia (TF). The sample size is unbalanced and incommensurable between gelfoam and other graft materials. In addition, a confounding factor was added in the gelfoam group, thereby affected the assessment of TM closure. Thus, the conclusion is not rigorous and scientific.